Firm boundaries and buyer-supplier match in market transaction: IT system procurement of U.S. credit unions - Yukako Ono; Junichi Suzuki (Federal Reserve Bank of Chicago, 2009)
By examining IT system procurement between U.S. Credit Unions (CUs) and IT vendors, we present descriptive analyses showing that firms' outsourcing decisions might be interrelated to each other through suppliers' market entry decisions. The buyer-supplier match in the market might also play an important role in determining firms' boundaries. We also argue that market thickness along the product space might determine the characteristics of input that is procured through the market.
Keywords: L22; L86; 330; firm boundaries; IT system; match; relationship-specific investment